Neonatal AKI profile using KDIGO guidelines: A cohort study in tertiary care hospital ICU of Lahore, Pakistan - Gul, Rafia; Anwar, Zahid; Sheikh, Mehmood; Salamat, Ayesha; Iqbal, Samer; Saleem, Furqan; Fatima, Samer (Frontiers in Pediatrics, 2022)
Abstract Background and objective Acute kidney injury (AKI) is observed in sick neonates and is associated with poor outcomes. Our cohort represents the neonatal characteristics diagnosed with AKI using KDIGO guidelines. Methodology A cohort study was conducted in the NICU of FMH from June 2019 to May 2021. Data were collected on standardized proforma. All continuous variables were not normally distributed and expressed as the median and interquartile range (IQR). Categorical variables were analyzed by proportional differences with the Pearson chi-square test or Fisher's exact tests. A multinomial logistic regression model was used to explore the independent risk factors of AKI. Time to the event (death) and the cohort's survival curves were plotted using the Cox proportional hazard model. Results AKI occurred in 473 (37.6%) neonates. The outborn birth (p 0.000, AOR 3.987, 95%CI 2.564 – 6.200), birth asphyxia (p 0.000, AOR 3.567, 95%CI 2.093 – 6.080), inotropic agent (p 0.000, AOR 2.060, 95%CI 1.436 – 2.957), antenatal steroids (p 0.002, AOR 1.721, 95%CI 1.213 – 2.443), central lines (p 0.005, AOR 1.630, 95%CI 1.155 – 2.298) and IVH/ICH/DIC (p 0.009, AOR1.580 , 95%CI 1.119 – 2.231). AKI significantly increases the duration of stay and mortality rates by 16.5% vs. 3.9% in neonates with normal renal function (p <0.001). Conclusion About one-third of critically sick neonates had AKI. Significant risk factors for AKI were outborn birth (298%), birth asphyxia (256%), inotropic agents (106%), NEC (74.7%), antenatal steroids (72%), central lines (63%), and IVH (58%). AKI prolongs the duration of stay and reduces the survival of sick neonates.